Effects of vacuum structure on neutron stars - Panda, P. K. [UNESP]; Sahu, R.; Mishra, S. (American Physical Society (APS), 2000)
We study the equation of state for neutron matter using the Walecka model including quantum corrections for baryons and sigma mesons through a realignment of the vacuum. We next use this equation of state to calculate the radius, mass, and other properties of rotating neutron stars. © 2000 The American Physical Society.